VARIOUS ASPECT OF ETHICAL MEDICAL PRACTICE: A REVIEW BASED ON AYURVEDA SCIENCE (International Journal of Ayurveda and Pharma Research, 2016)
Patients always seek for the quality treatment from his/her doctor. The basic tool of good medical practice involves professional competence, healthy relationships with patients and conductance of good ethical practice. The regulatory agencies composed â€œCode of Ethics and Professional Conductâ€ which is updated time to time. The guideline for Ayurvedic practice protect right of doctors as well as patient. The guideline of Ayurveda practice included information regarding how to practice with in confined regimen of standard protocol, it is very essential for a medical practitioner to follow ethical behavior since medical practice directly dealt with the health of human being. There are many ethical issue related to the medical profession adapted universally. Ayurveda the traditional science of Indian medical system also prescribed ethical code for the medical practice but yet to be recognized; thus there is a need to look at the ethical conductance of ayurveda practice to maintain quality of Ayurveda profession.